Ayurvedic Management of Karshya (Under Nutrition) – A Case Report - M.Chabanur, Sunilkumar; Dipankar, D.G. (Journal of Neonatal Surgery, 2025)
Karshya (under nutrition) is one of the burning problems in spite of many global wise remedial measures, which have been adopted to provide nutrition. A majority of the populations in the developing countries suffer from malnutrition and under nutrition. It forms one of the leading causes of mortality and morbidity in children as well as in adult populations. Karshya is a clinical condition that can be correlated with underweight in which body gets emaciated gradually. Among the eight socially undesirable physical state mentioned by Charak, Karshya has been categorized under nutritional deficiency.